Credibility of Indonesian politician as reflected in their speech - Hanafi Hanafi (Jurnal Linguistik Terapan, 2013)
Politician plays a very important role on the condition of our country especially related to communicating government’s programs or other phenomena happen in society. Politicians need not only knowledge and skills in their fields, but also strategies of communication. Demonstrations happen recently are, in part, caused by the failure of politicians in communicating some issues. It is the communication strategies, which determine whether or not a politician would positively or negatively impress the society. It is apparent that a language places an important role in determining his credibility. Using language adequately or appropriately is a prerequisite for them to look credible in the community. This article aims at investigating the felicity condition on the Indonesian politician’s performative utterances as written in newspaper and relating it to their credibility in society.